REVITALIZATION OF AL-ISLAMIC EDUCATION AND KEMUHAMMADIYAHAN IN COLLEGE OF MUHAMMADIYAH - Nurul, Ade; Elihami, Elihami (Al-Mirah: Jurnal Pendidikan Islam, 2019)
The journey of this nation is inseparable from the name of KHA Dahlan who founded Muhammadiyah. Muhammadiyah’s great role in nation building is reflected in all walks of life of the nation. The foundation of the Muhammadiyah movement on Dahlan’s study of reading the Qur’anic text and the Kauman Social context at that time, brought a big change for Indonesia and the World. The number of charity businesses in education reaches thousands and is spread throughout the country. This achievement is clearly in quantity very proud. This can be a challenge and an opportunity. The challenge to improve the quality of Muhammadiyah education and opportunities for Muhammadiyah’s cadre base. Muhammadiyah education has four functions, namely: First as a means of education and intelligence, Second, community service, preaching amar ma’ruf nahi munkar and Fourth, cadre land acquisition. The mission of Muhammadiyah’s education is at the same time a solution and response to the drying up of the religious spirit in education, Muhammadiyah has the characteristics of al-Islam and Kemuhammadiyahan education. These two things are characteristic as well as solutions in filling the spiritual spirit drought in education, both in primary and secondary education and in higher education in Muhammadiyah. All Muhammadiyah Charitable Enterprises (AUM) education must carry out the education of al-Islam and Kemuhammadiyahan as the foundation of education. AIK that has been running on Muhammadiyah institutions must be re-vital in its function. So that the four roles and the mission of Muhammadiyah’s education can work as expected. AIK revitalization is based on the reality that considers AIK less important in Muhammadiyah education. the weakening spirit that we need to immediately respond positively. Revitalization means, first, holding AIK for those in Muhammadiyah universities that do not yet exist, second, revitalizing the functioning of AIK that is already running. By considering several aspects. The educational objectives of the Muhammadiyah in the grand design of the plan that will encourage the realization of a progressive Indonesia must begin with the revitalization of AIK in the Muhammadiyah congregation.